Undergraduate Medical Education during Coronavirus Disease 19: Scope, Practices and Limitations in Developing Countries - Mosammat Kohinoor Parveen, MD Jafrul Hannan, Muhammad Hashim Ghouri, Wardah Anwar, Saima Tabassum, Zainab Farooq, Hira Abid, Muhammad Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Coronavirus Disease 19 has highly impacted the education system and created the trend of online classes. To fill in the gap created by lock down and to continue an uninterrupted learning process, educational institutions worldwide started organizing online classes. Although Medical education is mostly practice based but it was not safe to conduct on campus classes. This study aimed at measuring the scope and limitations of online education and the overall impacts of Coronavirus Disease 19 on the medical education system. Methodology: Cross-sectional study. Ethical approval was obtained from Ethical committee South Point Hospital. Informed consent was obtained. Self-administered questionnaires were given to the participants. Results: E-Learning opportunities were made available in 98.69% cases; some student forums also participated creating additional opportunities. Out of 260 students, 108 (41.1%) were males and 152 (57.8%) females. 29.3% belonged to Metropolitan Area, 28.9% to District Town, 16.3% to Upazila Town, 24.3% to village and 0.4% to unspecified areas. The quality of internet was reported as excellent, good, fair and poor. Only 1.9% of the students had more than 80% attendance. Zoom was used in 57.8% situations followed by Facebook live (15%) and was least for pre-recorded video upload, YouTube link etc. On investigation about quality of lectures, 8.7% people rated excellent while 75.7% students marked them fair to good and 14.8% rated as poor. 46.8% of students showed satisfaction towards online assessments and 44.5% students were not satisfied. Families of 57.4% respondents faced financial stress. 6.8% faced none whereas 29.3% students faced huge mental stress during Coronavirus Disease 19. Conclusions: E-learning is the new normal during Coronavirus Disease 19 pandemic. Given the opportunity, medical students although benefited a lot but there existed a technological divide. There were also financial and mental stresses to certain extent.